Chromosomal aneuploidies and copy number variations in posterior fossa abnormalities diagnosed by prenatal ultrasonography. (23rd October 2017) - Lei, Ting; Feng, Jie‐Ling; Xie, Ying‐Jun; Xie, Hong‐Ning; Zheng, Ju; Lin, Mei‐Fang
Abstract: Objective: To explore the genetic aetiology of fetal posterior fossa abnormalities (PFAs). Methods: This study involved cases of PFAs that were identified by prenatal ultrasonographic screening and confirmed postnatally between January 2012 and January 2016. Conventional cytogenetic analyses and chromosomal microarray analysis were performed, and chromosomal aneuploidies and copy number variations (CNVs) were identified. Results: Among 74 cases included in this study, 8 were of Blake's pouch cyst; 7, Dandy‐Walker malformation; 11, vermian hypoplasia; 32, enlarged cisterna magna; and 16, cerebellar hypoplasia. The rates of nonbenign chromosomal aberrations (including chromosomal aneuploidies, pathogenic CNVs, and variants of unknown significance) were 2/8 (25.0%), 2/7 (28.5%), 8/11 (72.7%), 7/32 (21.9%), and 6/16 (37.5%), respectively. Cases were also classified as isolated PFAs (30/74), PFAs with other central nervous system (CNS) abnormalities (13/74), or PFAs with extra‐CNS structural abnormalities (31/74). No fetuses with isolated PFAs or PFAs accompanied by other CNS abnormalities exhibited chromosomal aneuploidies or pathogenic CNVs. The rate of pathogenic chromosomal aberrations in the remaining fetuses was 17/31 (22.9%). Conclusion: The combined use of chromosomal microarray analysis and karyotype analysis might assist the prenatal diagnosis and management of PFAs, with extra‐CNS structural abnormalities being detected by ultrasonography. Abstract : What's already known about this topic? The prognosis of posterior fossa abnormalities (PFAs) varies considerably depending on the type of anomaly, and the risk of abnormal chromosomal karyotypes differs for each type of isolated PFA. what does this study add? This study highlights the addition of chromosomal microarray analysis in addition to karyotype analysis for the evaluation of genetic aetiology of various types of PFAs. We have also accounted for associated malformations into account by performing ultrasound anomaly scans.